UKHUWAH ISLAMIYAH DALAM PANDANGAN AL-QUR’AN - Herwani Herwani (Cross-border, 2020)
Brotherhood that exists between Muslims is called ukhuwah Islamiyah. As social beings, humans cannot be separated from interactions with other humans. In Islam, interactions among Muslims as well as interactions with non-Muslims have been regulated by the Qur'an and hadith as guidelines and instructions. A well-established ukhuwah will form an environment or society that is just, peaceful and prosperous. On the other hand, if the ukhuwah is not well established because it feels that the individual or group is the strongest and most powerful, it will lead to friction, hostility, revenge, and even war. Ukhuwah as taught in Islam is to accept every difference, and educate each individual to maintain harmony, help each other and complement each other. Differences that occur in humans are sunnatullah that must always be grateful for. This paper discusses ukhuwah Islamiyah in the view of the Qur'an. The main problem discussed in this paper is the concept of ukhuwh Islamiyah in the Qur'an surah al-Hujarat verses 10-13. The results and discussion show that ukhuwah Islamiyah is a great brotherhood or ownership of a strong bond between one another so that it feels like one body or one building. With ukhuwah will bring harmony, attachment and eliminate differences and enmity. The wisdom of ukhuwah Islamiyah is the formation of a sense of unity, justice, peace, harmony, security, justice and prosperity in social life.